THE RELATIONSHIP BETWEEN MENTAL HEALTH AND FUNCTIONAL CONSTIPATION AMONG ADOLESCENTS - Rokhayati, Evi; Adila Putri Istiqomah; Tri Oktaviyantini; Nur, Fadhilah Tia (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Constipation is a common digestive problem that is divided into primary (functional) and secondary. Functional constipation is diagnosed using the Rome IV criteria, which include symptoms such as straining, hard stools, incomplete defecation, and a sensation of anorectal obstruction. Adolescents, as a transitional phase of puberty, are vulnerable to mental health problems that can affect digestion. This study aimed to analyze the relationship between mental health and functional constipation in 308 grade 10 students of SMA Negeri 1 Surakarta (October 10, 2024) using a cross-sectional design. The independent variable was mental health (the Rome IV red flag question), while the dependent variable was functional constipation (Rome IV and BSFS). Chi-square analysis showed a significant association between depression and functional constipation (p=0.006; OR 4.09; 95% CI 1.403–11.913). Psychological conditions have been shown to trigger constipation, so early detection, prevention, and counseling with parents, teachers, and health professionals are important to improve the quality of life of adolescents.